2000
DOI: 10.5380/rsa.v1i1.996
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização Sorológica E Molecular De Rotavírus De Suínos Na Região Sul Do Brasil

Abstract: O objetivo do estudo foi realizar a caracterização sorológica e molecular em amostras de rotavírus suíno na região Sul do Brasil. Para sua realização, foram colhidas 167 amostras de fezes de suínos nas fases de maternidade e creche em 52 granjas de produção de suínos que apresentavam freqüentes casos de diarréia, em 14 municípios dos Estados do Rio Grande do Sul, Santa Catarina e Paraná, durante o período compreendido entre junho de 1995 e outubro de 1997. Todas as amostras foram submetidas a um ensaio imunoen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…While G9 was not recorded in studies from Belém, G3 and G5 were found to be common genotypes in piglets. The P [6] genotype was predominant in all the studies from Southern Brazil 9,35,42 . Tonietti et al 43 related the first detection of P [23] genotype in Brazil associated with G5 in samples that were collected in 2011, however P [23] genotype of this present study were collected in 2008, showing that this P-type has circulated before in Northern Region, furthermore this is the first reported case of G3P [23] combination in Brazil.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…While G9 was not recorded in studies from Belém, G3 and G5 were found to be common genotypes in piglets. The P [6] genotype was predominant in all the studies from Southern Brazil 9,35,42 . Tonietti et al 43 related the first detection of P [23] genotype in Brazil associated with G5 in samples that were collected in 2011, however P [23] genotype of this present study were collected in 2008, showing that this P-type has circulated before in Northern Region, furthermore this is the first reported case of G3P [23] combination in Brazil.…”
Section: Discussionmentioning
confidence: 90%
“…It was the first study conducted in Northern Brazil about swine where the occurrence of rotaviruses was confirmed with an infection rate of 9.9%. In Southern Brazil, Kroeff 9 has recovered PoRV-A from 35.3% of the nursing/weaning piglets sampled. This comparatively high infection rate was found even with the best management and hygiene conditions, and productivity in compared to the facilities analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations